PENGARUH MEDIA TANAM TERHADAP AKLIMATISASI ANGGREK BULAN (Phalaenopsis amabilis L.) DENGAN PENAMBAHAN PUPUK GROWMORE - Nursaumi, Novi; Sarjani, Tri Mustika; Ariska, Raja Novi (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2025)
This research aims to determine the effect of planting media on the acclimatization of moon orchids (Phalaenopsis amabilis L.) with the addition of Growmore fertilizer. The method used is a quantitative experimental method and treatments are implemented using a Completely Randomized Design (CRD). The data analysis technique used is the one-way ANOVA test with Î±= 0.05 and the Duncan Multiple Range Test (DMRT 5%). The results of this study showed that there was a significant influence on the growth parameters of leaf length (sig. 0.001), plant height (sig. 0.001), root length (sig. 0.004), and number of roots (sig. 0.015). The best treatment for the growth parameters of leaf length and plant height was shown by the P3 treatment (a mixture of 25 grams of chopped fern media and 75 grams of wood charcoal with the addition of 2 grams/liter of Growmore fertilizer). In comparison, the best treatment for the growth parameters of root length and number of roots was shown by the treatment P2 (mixture of 25 grams of sphagnum moss media and 75 grams of wood charcoal with the addition of 2 grams/liter of Growmore fertilizer). However, it did not significantly affect the leaf number growth parameters. Keywords: Acclimatization, Planting Media, Growmore Fertilizer, Phalaenopsis amabilis L.